Immunohistochemical Study of the PD-1/PD-L1 Pathway in Cutaneous Lupus Erythematosus - Zsófia Király; Ágota Szepesi; Anna Sebestyén; Enikő Kuroli; Enikő Kuroli; Fanni Rencz; Béla Tóth; Laura Bokor; József Szakonyi; Márta Medvecz; Bernadett Hidvégi (Frontiers Media S.A., 2022)
The pathomechanism of various autoimmune diseases is known to be associated with the altered function of programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) axis. We aimed to investigate the role of this pathway and inflammatory cell markers in subtypes of cutaneous lupus erythematosus (CLE): discoid lupus erythematosus (DLE), subacute CLE (SCLE) and toxic epidermal necrolysis (TEN)-like lupus, a hyperacute form of acute CLE (ACLE). Ten skin biopsy samples from 9 patients were analyzed with immunohistochemistry regarding the following markers: CD3, CD4, CD8, Granzyme B, CD123, CD163, PD-1, PD-L1. Our group consisted of 4 SCLE (2 idiopathic (I-SCLE) and 2 PD-1 inhibitor-induced (DI-SCLE)), 4 DLE and 1 TEN-like lupus cases. From the latter patient two consecutive biopsies were obtained 1 week apart. Marker expression patterns were compared through descriptive analysis. Higher median keratinocyte (KC) PD-L1 expression was observed in the SCLE group compared to the DLE group (65% and 5%, respectively). Medians of dermal CD4, Granzyme B (GB), PD-1 positive cell numbers and GB+/CD8+ ratio were higher in the DLE group than in the SCLE group. The I-SCLE and DI-SCLE cases showed many similarities, however KC PD-L1 expression and dermal GB positive cell number was higher in the former. The consecutive samples of the TEN-like lupus patient showed an increase by time within the number of infiltrating GB+ cytotoxic T-cells and KC PD-L1 expression (from 22 to 43 and 30%-70%, respectively). Alterations of the PD-1/PD-L1 axis seems to play a role in the pathogenesis of CLE.